Standing soldiers, kneeling slaves : race, war, and monument in nineteenth-century America - Savage, Kirk, 1958- (Princeton University Press, 2018)
"The United States began as a slave society, holding millions of Africans and their descendants in bondage, and remained so until a civil war took the lives of a half million soldiers, some once slaves themselves. Standing Soldiers, Kneeling Slaves explores how the history of slavery and its violent end was told in public spaces--specifically in the sculptural monuments that came to dominate streets, parks, and town squares in nineteenth-century America. Looking at monuments built and unbuilt, Kirk Savage shows how the greatest era of monument building in American history took place amid struggles over race, gender, and collective memory. Standing Soldiers, Kneeling Slaves probes a host of fascinating questions and remains the only sustained investigation of post-Civil War monument building as a process of national and racial definition. Featuring a new preface by the author that reflects on recent events surrounding the meaning of these monuments, and new photography and illustrations throughout, this new and expanded edition reveals how monuments exposed the myth of a "united" people, and have only become more controversial with the passage of time."--